(untitled) (Research, Society and Development, 2021)
Competition with weeds for water or light can affect physiological parameters of the crops of interest. From this study, the objective was to evaluate the effect of soil moisture and the competition of two weed species in different combinations on the physiological characteristics of eucalyptus plants. The experimental design used was randomized with four replications in a 4 x 4 factorial scheme. The first factor corresponded to the combinations of eucalyptus clonal hybrid plants grown in competition with black sting and brachiaria: 1 - One eucalyptus plant + two brachiaria plants per pot; 2 - One eucalyptus plant + two black sting per pot; 3 - One eucalyptus plant + one black sting plant + one brachiaria plant per pot, and; 4 - one eucalyptus plant per pot. The second corresponded to soil water levels: 100, 74, 67 and 60% of field capacity. Evaluations of chlorophyll a, b, a/b and total contents were made, as well as variables related to chlorophyll fluorescence. The eucalyptus growing alone showed higher values of chlorophyll a chlorophyll b and total chlorophyll. The chlorophyll a/b ratio was lower at all soil moisture levels. The initial fluorescence showed a tendency to decrease with increasing humidity. At the lowest moisture levels tested, the eucalyptus plants were under stress condition with variable fluorescence/maximum fluorescence values below 0.75.